Vpliv mazalnih razmer na tribološko vedenje materialov tesnilnih obročev v mehanskih drsnih tesnilih - Vezjak, Anton (Materiali in tehnologije, 2002)
The most important aspect of development of the mechanical seals is the tribological design of the seal faces. Tribological design involves, among other things, the selection of materials and defining the tribological characteristics of the sealing pair within the working limits. The performance of a mechanical face seal depends on many factors, of which lubrication has one of the most crucial roles. In this paper the influence of various lubricating conditions on different tribological parameters is analysed. Short-interval PV tests were performed on a computer-controlled test rig of our own design, where eight parameters were monitored online. Commercially available alumina, stainless steel and carbon-graphite were tested in tap water. The results show that for all material pairs, tribological parameters such as friction coefficient, the wear and the pressure-velocity limit are affected by lubricating conditions in the sealing dam.
Keywords: tesnila drsna; tesnila mehanska; mazanje; trenje; obraba; tribologija; tesnila